DEVELOPMENT OF RADAR environment GEOPHYSICAL MONITORING in order to improve aviation safety - A. L. Rybalkina; A. S. Spirin (Научный вестник МГТУ ГА, 2016)
The article contains the statistics analyzes of accidents associated with adverse external conditions, including weather conditions, for seven years. On the analysis basis insufficient supply of final consumers meteorologic data is concluded. One of the ways to improve meteorological support of Unified air traffic management system consolidated centers by creating regional centers of processing radar information for conducting environment geophysical monitoring is suggested.